A novel love story eaudiobook - Poston, Ashley (Books on Tape, 2024)
NEW YORK TIMES BESTSELLER ∙ A professor of literature finds herself caught up in a work of fiction . . . literally, from the New York Times bestselling author of The Seven Year Slip and The Dead Romantics. Eileen Merriweather loves to get lost in a good happily-ever-after. The fictional kind, anyway. Because at least imaginary men don’t leave you at the altar. She feels safe in a book. At home. Which might be why she’s so set on going her annual book club retreat this year—she needs good friends, cheap wine, and grand romantic gestures—no matter what. But when her car unexpectedly breaks down on the way, she finds herself stranded in a quaint town that feels like it’s right out of a novel . . . Because it is . This place can’t be real, and yet… she’s here, in Eloraton, the town of her favorite romance series, where the candy store’s honey taffy is always sweet, the local bar’s burgers are always a little burnt, and rain always comes in the afternoon. It feels like home. It’s perfect—and perfectly frozen, trapped in the late author’s last unfinished story. Elsy is sure that’s why she must be here: to help bring the town to its storybook ending. Except there is a character in Eloraton that she can’t place—a grumpy bookstore owner with mint-green eyes, an irritatingly sexy mouth and impeccable taste in novels. And he does not want her finishing this book. Which is a problem because Elsy is beginning to think the town’s happily-ever-after might just be intertwined with her own.